1.
x/3 + y/5 = 5
x/2 = y/3 - 2
x/3 + y/5 = 5 | *15
x/2 -y/3 = -2 | * 6
5x + 3y = 75 | *2
3x - 2y = -12 | *3
10x + 6y = 150
9x -6y = -36
10x + 9x = 150 - 36
19x = 114
x = 6
6/3 + y/5 = 5
2 + y/5 = 5
y/5 = 3
y + 15
x = 6
y = 15
2.
(2x)/5 + y/3 = 1 | *15
x/2 - (2y)/9 = -9/2 | *18
6x + 5y = 15 | * 4
9x - 4y = -81 | * 5
24x + 20y = 60
45x - 20y = -405
24x + 45x = 60 - 405
69x = -345
x = -5
6 * (-5) + 5y = 15
-30 + 5y = 15
5y = 45
y = 9
x = 5
y = 9
3.
2/3x - 1/9y = 6 | *9
0,5y = 3x - 5
6x - y = 54 | * (0,5)
-3x + 0,5y = -5 | *1
3x - 0,5y = 27
-3x + 0,5y = 27
0 = 27
równanie sprzeczne